Cortical reorganization after motor stroke: A pilot study on differences between the upper and lower limbs. Issue 4 (9th November 2020) - Binder, Ellen; Leimbach, Martha; Pool, Eva‐Maria; Volz, Lukas J.; Eickhoff, Simon B.; Fink, Gereon R.; Grefkes, Christian
Abstract: Stroke patients suffering from hemiparesis may show substantial recovery in the first months poststroke due to neural reorganization. While reorganization driving improvement of upper hand motor function has been frequently investigated, much less is known about the changes underlying recovery of lower limb function. We, therefore, investigated neural network dynamics giving rise to movements of both the hands and feet in 12 well‐recovered left‐hemispheric chronic stroke patients and 12 healthy participants using a functional magnetic resonance imaging sparse sampling design and dynamic causal modeling (DCM). We found that the level of neural activity underlying movements of the affected right hand and foot positively correlated with residual motor impairment, in both ipsilesional and contralesional premotor as well as left primary motor (M1) regions. Furthermore, M1 representations of the affected limb showed significantly stronger increase in BOLD activity compared to healthy controls and compared to the respective other limb. DCM revealed reduced endogenous connectivity of M1 of both limbs in patients compared to controls. However, when testing for the specific effect of movement on interregional connectivity, interhemispheric inhibition of the contralesional M1 during movements of the affected hand was not detected in patients whereas no differences in condition‐dependent connectivity were found for foot movements compared to controls. In contrast, both groups featured positive interhemispheric M1 coupling, that is, facilitation of neural activity, mediating movements of the affected foot. These exploratory findings help to explain why functional recovery of the upper and lower limbs often develops differently after stroke, supporting limb‐specific rehabilitative strategies. Abstract : The present pilot study aimed to gain insights into the neural reorganization patterns of lower limb motor function in comparison to upper limb function in well‐recovered chronic stroke patients compared to healthy participants using functional magnetic resonance imaging and dynamic causal modeling. For the first time, we thus investigated unilateral movements of both the hands and feet in one common paradigm. This enabled direct comparisons of the respective reorganization patterns underlying hand and foot movements as well as differential conclusions regarding their functional relevance.